Pembrolizumab-Induced Isolated Cranial Neuropathy: A Rare Case Report and Review of Literature - Bruno, Francesco; Palmiero, Rosa Antonietta; Ferrero, Bruno; Franchino, Federica; Pellerino, Alessia; Milanesi, Enrica; Soffietti, Riccardo; Rudà, Roberta (Frontiers in Neurology, 2021)
Introduction: Anti-PD1 agents are widely used in the treatment of solid tumors. This has prompted the recognition of a class of immune-related adverse events (irAEs), due to the activation of autoimmune T-cells. Pembrolizumab is an anti-PD1 agent, which has been related to an increased risk of various neurological irAE (n-irAEs). Here, we present a rare case of pembrolizumab-induced neuropathy of cranial nerves. Case Report: A 72-year-old patient was diagnosed with a lung adenocarcinoma in February 2018 (EGFR–, ALK–, and PDL1 90%). According to the molecular profile, pembrolizumab was started. After three administrations, the patient developed facial paresis, ptosis, ophthalmoplegia, and dysphonia. As brain metastases and paraneoplastic markers were excluded, a drug-related disorder was suspected and pembrolizumab was discontinued. A nerve conduction study and electromyography excluded signs of neuropathy and myopathy at four limbs, and repetitive nerve stimulation was negative. However, altered blink reflex and nerve facial conduction were consistent with an acute neuropathy of the cranial district. Thus, the patient was treated with two cycles of intravenous immunoglobulins (IVIg), which rapidly allowed improvement of both symptoms and neurophysiological parameters. However, the patient died in October 2018 for a progression of lung tumor. Discussion: Only 16 cases of pembrolizumab-related neuropathies have been described so far. Our case is of particular interest for the isolated involvement of cranial nerves and the prompt response to IVIg. Conclusion: N-irAEs are insidious conditions that require solid knowledge of onco-immunotherapy complications: it is mandatory not to delay any treatment that would potentially modify the course of a neurological complication.